2015
DOI: 10.3390/ijms160612713
|View full text |Cite
|
Sign up to set email alerts
|

The Stable Level of Glutamine synthetase 2 Plays an Important Role in Rice Growth and in Carbon-Nitrogen Metabolic Balance

Abstract: Glutamine synthetase 2 (GS2) is a key enzyme involved in the ammonium metabolism in plant leaves. In our previous study, we obtained GS2-cosuppressed plants, which displayed a normal growth phenotype at the seedling stage, while at the tillering stage they showed a chlorosis phenotype. In this study, to investigate the chlorosis mechanism, we systematically analyzed the plant growth, carbon-nitrogen metabolism and gene expressions between the GS2-cosuppressed rice and wild-type plants. The results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…Previous study has found that transgenic rice overexpressing a chloroplastic GS gene showed enhanced tolerance to salt stress (Hoshida et al 2000). Moreover, a recent study has revealed that stable level of chloroplastic GS plays an important role in rice growth and carbon-nitrogen metabolic balance (Bao et al 2015). Therefore, it could be postulated that proline supply has increased the cellular proline concentration and subsequently affected the interregulation of plant metabolism, which was certainly important in relation to plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has found that transgenic rice overexpressing a chloroplastic GS gene showed enhanced tolerance to salt stress (Hoshida et al 2000). Moreover, a recent study has revealed that stable level of chloroplastic GS plays an important role in rice growth and carbon-nitrogen metabolic balance (Bao et al 2015). Therefore, it could be postulated that proline supply has increased the cellular proline concentration and subsequently affected the interregulation of plant metabolism, which was certainly important in relation to plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…4 Carbohydrates also serve as carbon skeletons and a source of energy for plants to assimilate ammonium (NH 4 + ). 5…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids, glycosides, polysaccharides, and organic acids are contained in many biostimulants and they may act as precursors or activators of endogenous plant hormones [20]. Abscisic acid (ABA) is involved in embryogenesis, seed physiology reactions, plant growth, and biotic and abiotic stress tolerance [36]. Young tissues have high ABA levels, although ABA has historically been considered a growth inhibitor [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Abscisic acid (ABA) is involved in embryogenesis, seed physiology reactions, plant growth, and biotic and abiotic stress tolerance [36]. Young tissues have high ABA levels, although ABA has historically been considered a growth inhibitor [36,37]. It has been shown that ABA-deficient mutant plants are severely stunted and conversely exogenous ABA treatment of mutants restores normal cell expansion and growth [37].…”
Section: Discussionmentioning
confidence: 99%